Rheumatoid pericardial effusion with heart block treated by pericardiectomy and implantation of permanent pacemaker. Issue 1 (January 1977) - Gelson, A; Sanderson, J M; Carson, P
Abstract : A patient with long-standing seropositive erosive rheumatoid arthritis developed a pericardial effusion with chronic cardiac tamponade. He had evidence of conducting system disease and developed heart block. He was successfully treated by pericardiectomy and implantation of a demand pacemaker.